An Analysis of Imagery in Mother Africa, May I Return? Poem by Janaya Cooper - Dedi Efendi; Dodi Oktariza (Jurnal Ilmiah Langue and Parole, 2023)
This research analyzed about imageries in the Mother Africa, May I Return? poem. The poem of Black Live Matter (BLM) movement in America, United Kingdom and Australia. The purpose of this research is to describe the kinds of imageries found in the Mother Africa, May I Return? poem. In this research, the writer used the descriptive qualitative method and used theory of Imagery by Perrine (1992). Data are explained by find the meaning and described them based on the kinds of imagery through four procedure, they are: identifying, classiying, analyzing and making the conclusion from the data. The result of this research are the writer found about 13 data of imagery of the poem. Visual imagery is the most dominant imagery in the Mother Africa, May I Return? poem. There are 6 data of visual imagery from 13 total data that the writer found in the poem, because visual imagery is the appropriate imagery for BLM’s proponents to describe their misery in their own country. Another imagery that the writer also found in this poem are auditory imagery, tactile imagery and kinaesthetic imagery. There are 5 data of auditory imagery, 2 data of tactile imagery and 1 data of kinaesthetic imagery found in the Mother Africa, May I Return? poem.